证明:(a+b)^2/2+(a+b)/4 =(a^2+b^2)/2+ab+(a+b)/4 因为a^2+b^2≥2ab 所以(a^2+b^2)/2+ab+(a+b)/4≥2ab/2+ab+(a+b)/4=2ab+(a+b)/4
已知a,b,c∈R+,求证:(a+b)2/2+(a+b)/4≥a√b+b√a
1个回答
相关问题
-
已知abc∈R,求证b^2/a+c^2/b+a^2/c≥c√b/a+a√c/b+b√a/c
-
已知(a-b)^2=4(a-b)(b-c),求证:a+c=2b
-
已知a,b∈R求证:a^2 + b^2 + a*b +1 > a + b
-
已知a,b,c属于R求证:b^2c^2+c^2a^2+a^2b^2>=abc(a+b+c)
-
已知4(a-b)(b-c)-(a-c)^2=0,求证:2b=a+c.
-
已知a,b∈R,求证2(a2+b2)≥(a+b)2.
-
已知a,b∈R,求证2(a2+b2)≥(a+b)2.
-
已知a,b,c∈R+,求证:(a/b+b/c+c/a)(b/a+c/b+a/c)>=9
-
已知abc∈R* 求证.a(a^2+b^2)+b(c^2+a^2)+c(a^2+b^2)≥6abc
-
已知a、b、c∈R,且a+b+c=1求证:.a∧2+b∧2+c∧2≥1/3